Multiple Dirac cones at the surface of the topological metal LaBi - Nayak, Jayita; Wu, Shu-Chun; Kumar, Nitesh; Shekhar, Chandra; Singh, Sanjay; Fink, Joerg; Rienks, Emile E. D.; Fecher, Gerhard H.; Parkin, Stuart S. P.; Yan, Binghai; Felser, Claudia (Nature Communications, 2017)
The rare-earth monopnictide LaBi exhibits exotic magneto-transport properties, including an extremely large and anisotropic magnetoresistance. Experimental evidence for topological surface states is still missing although band inversions have been postulated to induce a topological phase in LaBi. In this work, we have revealed the existence of surface states of LaBi through the observation of three Dirac cones: two coexist at the corners and one appears at the centre of the Brillouin zone, by employing angle-resolved photoemission spectroscopy in conjunction with ab initio calculations. The odd number of surface Dirac cones is a direct consequence of the odd number of band inversions in the bulk band structure, thereby proving that LaBi is a topological, compensated semimetal, which is equivalent to a time-reversal invariant topological insulator. Our findings provide insight into the topological surface states of LaBi's semi-metallicity and related magneto-transport properties.
CRIS-Team Scopus Importer:2022-04-14